From collection to community to collections again: Urban Indigenous women, material culture and belonging. (September 2016) - Krmpotich, Cara; Howard, Heather; Knight, Emma
First Story Toronto – a community organization dedicated to the Indigenous histories of Toronto, Canada – is steward to a collection of items mostly made and collected during the 20th century. With origins in the Anglican Church Women, the collection reflects a time when policies and actions of the state and churches internalized colonial processes within Canada. Yet the donation of the ACW material to a Native woman and housing advocate in 1976 hints at the shifting political and cultural contexts of this collection. Native crafts were used by Indigenous women in the city in displays of both Indigenous sovereignty and multiculturalism. Recently, the collection has been taken up by another group of Indigenous women in the Memory, Meaning-Making and Collections project. Handling sessions with artefacts and 'talking circles', initially designed to research the role of objects in collective memory and life-history processes, have been appropriated by the participating seniors toward their own goals. The collection has become a source of continuing education, sparking the women to teach and learn beadwork and quillwork; compare life experiences among urban Indigenous people; question history-making processes; and visit museum stores to handle collections and learn with curators. The histories intersecting with this collection thus push back against a range of tropes, provide more nuanced insights into the lives and values of urban Indigenous women in Canada, and the ways collections are used in articulations of belonging among Indigenous peoples.